2022
DOI: 10.1155/2022/9112127
|View full text |Cite
|
Sign up to set email alerts
|

Fyn Signaling in Ischemia-Reperfusion Injury: Potential and Therapeutic Implications

Abstract: Ischemic stroke caused by arterial occlusion is the most common type of stroke and is one of the leading causes of disability and death, with the incidence increasing each year. Fyn is a nonreceptor tyrosine kinase belonging to the Src family of kinases (SFKs), which is related to many normal and pathological processes of the nervous system, including neurodevelopment and disease progression. In recent years, more and more evidence suggests that Fyn may be closely related to cerebral ischemia-reperfusion, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Considering that FYN may regulate the process of cerebral I/R, 14 we also designed related experiments to ascertain the specific effects of FYN on cerebral I/R injury. It was reported that the shortage of FYN contributed to the suppression of OS in diabetic renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering that FYN may regulate the process of cerebral I/R, 14 we also designed related experiments to ascertain the specific effects of FYN on cerebral I/R injury. It was reported that the shortage of FYN contributed to the suppression of OS in diabetic renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“… 43 , 44 Our data proved that FYN was upregulated after tMCAO/R treatment and FTO overexpression reduced FYN expression by decreasing FYN mRNA m6A modification. Considering that FYN may regulate the process of cerebral I/R, 14 we also designed related experiments to ascertain the specific effects of FYN on cerebral I/R injury. It was reported that the shortage of FYN contributed to the suppression of OS in diabetic renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the role of Fyn/Src kinases in cell proliferation, saracatinib has been in clinical trials for various types of cancers, such as bone, ovarian, and breast cancer (7)(8)(9). Excessive production of Fyn/Src and its phosphorylation in reactive glial cells or neurons causes hyperexcitability, neuroinflammation, and neurodegeneration (10,11). Therefore, saracatinib has been tested as a disease modifier in experimental models of epilepsy and AD (3,12) and in clinical trials for AD and Parkinson's disease (13,14).…”
Section: Introductionmentioning
confidence: 99%